Pengaruh Penambahan Gelling Agent Carbopol Dan Asam Stearat terhadap Nilai Kalor Etanol Gel - Erlinda Ningsih; Kartika Udyani; Dian Agus Saputra; Silvi Natalia Fadilatut Talcha (Journal of Industrial Process and Chemical Engineering (JOICHE), 2021)
Ethanol gel is a semisolid fuel made from ethanol by mixing the gelling agent.Ethanol gel has the advantage of facilitating packaging, distribution and storagebecause it does not spill and flow easily. Another advantage of ethanol gel is that itdoes not smoke during the combustion process, does not cause soot and does notproduce harmful gases. This research aims to compare the 2 best gelling agentsand study the effect of adding the gelling agent to the calorific value. The processof making ethanol gel begins by inserting a gelling agent of 4-12% w into a beakerglass. Then add 20 ml of distilled water while stirring until the solution thickens.After that, slowly put 75 grams of 95% ethanol into the beaker which alreadycontains the gelling agent solution. For the manufacture of ethanol gel with astearic acid gelling agent, heating is done first in making the solution and left for 3hours after mixing with ethanol. Based on the analysis, it was found that thehighest calorific value was 12052.7 cal / g with stearic acid gelling agent in theaddition of 12% (% w).